Let’s Discuss About Men’s Rights, Because Women’s Rights Have Been Discussed Too Often Case Study: Social Movement, Fighting for Men’s Rights in India - Tasya Amalia Fitri (International Journal of Social Sciences Review, 2021)
This study discusses the men’s rights movement raised by Men’s Rights Activist in India. The main problem is the abuse of law and crime relating to marriage and domestic violence by women to overthrow men. The purpose of this study is to analyze what is the purpose of the emergence of Men’s Rights Movement in India. The theory used is the new social movement and human rights. The method used is a qualitative method with the study of documentation and literature as data collection. The results of the analysis was found that this movement aimed at obtaining legal justice in the new gender equality law, because now women use it to make false accusations and use the law against their husbands as mere retribution. Therefore, in my opinion the discourse of the Men’s Rights Movement is something interesting to be explored, because this has something to do with human rights.